2018
DOI: 10.1111/dmcn.14071
|View full text |Cite
|
Sign up to set email alerts
|

Measuring change in gait performance of children with motor disorders: assessing the Functional Mobility Scale and the Gillette Functional Assessment Questionnaire walking scale

Abstract: Aim To examine the responsiveness and minimal important change (MIC) of two gait performance measures, the Functional Mobility Scale (FMS) and the Gillette Functional Assessment Questionnaire walking scale (FAQ), in a paediatric inpatient setting. Method Sixty‐four children and adolescents with a motor disorder, including cerebral palsy, traumatic brain injury, or stroke (25 females, 39 males; mean age [SD] 12y 6mo [3y 2mo], range 6–18y 6mo), were recruited. Physiotherapists scored the FMS and FAQ at the start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…Gait assessment may contribute to diagnosis, describe the natural history or categorise the severity of pathology 2 3. It is also used as an outcome to demonstrate the efficacy of surgery, therapy or medications 4 5…”
Section: Introductionmentioning
confidence: 99%
“…Gait assessment may contribute to diagnosis, describe the natural history or categorise the severity of pathology 2 3. It is also used as an outcome to demonstrate the efficacy of surgery, therapy or medications 4 5…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore Ammann-Reiffer et al. ( 2019 ) reported that a change of 1 FMS level is a clinically meaningful change in the rehabilitation of gait performance in children with motor disorders, though not exclusively CP. The Gillette Functional Assessment Questionnaire has proven sensitive and detected improved function after surgery (Novacheck et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ammann‐Reiffer et al . examine the responsiveness and minimal important change (MIC) of the Functional Mobility Scale (FMS) and the walking scale portion of the Gillette Functional Assessment Questionnaire (FAQ‐w) in a pediatric inpatient setting . The prospective longitudinal psychometric study used ‘a construct and criterion approach to evaluate responsiveness and an anchor‐based approach to assess the minimal important change’ for each measure.…”
mentioning
confidence: 99%
“…Ammann-Reiffer et al 1 examine the responsiveness and minimal important change (MIC) of the Functional Mobility Scale (FMS) 2 and the walking scale portion of the Gillette Functional Assessment Questionnaire 3 (FAQ-w) in a pediatric inpatient setting. 1 The prospective longitudinal psychometric study used 'a construct and criterion approach to evaluate responsiveness and an anchor-based approach to assess the minimal important change' for each measure. This study represents an important addition to the body of work on these commonly used instruments as responsiveness in an inpatient setting has not previously been reported.The pediatric inpatient rehabilitation setting presents unique challenges to research.…”
mentioning
confidence: 99%
See 1 more Smart Citation